2020
DOI: 10.1101/2020.07.14.20153429
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 Pandemic among Latinx Farmworker and Non-farmworker Families in North Carolina: Knowledge, Risk Perceptions, and Preventive Behaviors

Abstract: (1) Background: The COVID-19 pandemic poses substantial threats to Latinx farmworkers and other immigrants in food production and processing. Classified as essential, such workers cannot shelter at home. Therefore, knowledge and preventive behaviors are important to reduce COVID-19 spread in the community. (2) Methods: Respondents for 67 families with at least one farmworker (FWF) and 38 comparable families with no farmworkers (non-FWF) in North Carolina completed a telephone survey in May, 2020. The survey… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…Mental health data gathered nationally early in the pandemic show increased effects on mental health 32 and suggest that the effects will result in more mental health impairment in disadvantaged groups, such as immigrants, as they cope with greater financial insecurity and grief caused by greater pandemic morbidity and mortality. 33 In addition, we have shown elsewhere 10 that these women are well informed about the causes of COVID-19 and recommended practices to prevent it. Their comments here reflect this knowledge and their inability to practice some of the methods to prevent COVID-19 in their families.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Mental health data gathered nationally early in the pandemic show increased effects on mental health 32 and suggest that the effects will result in more mental health impairment in disadvantaged groups, such as immigrants, as they cope with greater financial insecurity and grief caused by greater pandemic morbidity and mortality. 33 In addition, we have shown elsewhere 10 that these women are well informed about the causes of COVID-19 and recommended practices to prevent it. Their comments here reflect this knowledge and their inability to practice some of the methods to prevent COVID-19 in their families.…”
Section: Discussionmentioning
confidence: 93%
“…7-9 In addition, many immigrants live in crowded housing and multi-family dwellings that do not permit social distancing. 10 These risk factors for exposure to COVID-19 are exacerbated by the fact that many immigrants have low incomes, cannot communicate well in English, and lack documentation status to be in the US and to access health and income safety net programs. 11,12 For many immigrants, even if their particular job is not deemed essential, their low incomes and limited savings force them to continue working.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…More specifically, in COFS, 63% of farmworkers had more difficulty paying rent, 60% paying utilities, and 70% buying food during the pandemic (Rick Mines, Personal Communication, December 5, 2020), and overall, 52% of farmworkers reported a decrease in employment. 21 The economic impact on farmworkers and their families is not limited to California in that smaller studies in Oregon 22 and North Carolina 23 reported similar loss of employment and economic hardship among farmworkers.…”
Section: Discussionmentioning
confidence: 99%